2005
DOI: 10.1007/s00426-005-0037-z
|View full text |Cite
|
Sign up to set email alerts
|

The manifestation of attentional capture: facilitation or IOR depending on task demands

Abstract: Orienting attention exogenously to a location can have two different consequences on processing subsequent stimuli appearing at that location: positive (facilitation) at short intervals and negative (inhibition of return) at long ones. In the present experiments, we manipulated the frequency of targets and responses associated with them. Results showed that, even at long SOAs, where IOR is usually observed, facilitation was observed for infrequent targets at the same time that IOR was measured for frequent tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 26 publications
6
45
0
2
Order By: Relevance
“…On the other hand, for the identityuncued auditory targets in the PN-modality-different condition, modality-based inhibition occurred only in Experiment 1, but not in Experiment 2. The existence of repetition inhibition is determined not only by the physical match between the prime and the target, but also by the attentional set participants have adopted in the tasks at hand (Chen, Fuentes, & Zhou, 2010;Chen, Zhang, & Zhou, 2007;Lupiáñez et al, 2001;Lupiáñez et al 2007;Milliken et al, 2000). Since the modality of the prime was blocked in Experiment 1, so that the participants were fully aware that the prime modality was uninformative with regard to the target, the participants could adopt a sustained inhibitory tendency toward the blocked modality throughout the task block.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, for the identityuncued auditory targets in the PN-modality-different condition, modality-based inhibition occurred only in Experiment 1, but not in Experiment 2. The existence of repetition inhibition is determined not only by the physical match between the prime and the target, but also by the attentional set participants have adopted in the tasks at hand (Chen, Fuentes, & Zhou, 2010;Chen, Zhang, & Zhou, 2007;Lupiáñez et al, 2001;Lupiáñez et al 2007;Milliken et al, 2000). Since the modality of the prime was blocked in Experiment 1, so that the participants were fully aware that the prime modality was uninformative with regard to the target, the participants could adopt a sustained inhibitory tendency toward the blocked modality throughout the task block.…”
Section: Discussionmentioning
confidence: 99%
“…A cue back to fixation terminates the orienting response generated by the peripheral cue, hasten- of object-file integration (see Kahneman, Treisman, & Gibbs, 1992), in which current perceptual information is integrated with the memory representations of prior experience. They emphasize that on uncued trials, the onset of the target is spatially distinct from the onset of the cue; on cued trials, the lack of spatial distinctiveness encourages the integration of the two events (Lupiáñez et al, 2007). These ideas are all inherent in the habituation account and share considerable overlap with Sokolov's (1963) comparator theory of habituation.…”
Section: Habituation Recoveredmentioning
confidence: 99%
“…Lupiáñez and Milliken (1999) and their colleagues (Lupiáñez et al, 2001;Lupiáñez, Ruz, Funes, & Milliken, 2007) In all panels, the response being measured is a hypothetical continuous response that can represent either the sensory component or the motor component of the orienting reflex. It is location specific and peaks shortly after the presentation of the cue (C1).…”
Section: Habituation Recoveredmentioning
confidence: 99%
“…Lupiáñez and colleagues have consistently demonstrated that facilitation is larger in magnitude in discrimination than in detection tasks. Moreover, IOR emerges at longer cue-target intervals, and is smaller in size, in discrimination than in detection tasks (Lupiáñez, Milán, Tornay, Madrid, & Tudela, 1997;Lupiáñez & Milliken, 1999;Lupiáñez, Ruz, Funes, & Milliken, 2007). A review of the literature on cueing effects with detection tasks indicates that, contrary to IOR, which is an extremely robust effect when participants detect the appearance of targets, the occurrence of early facilitation is difficult to observe (see, e.g., Collie, Maruff, Yucel, Danckert, & Currie, 2000;Mele, Savazzi, Marzi, & Berlucchi, 2008;Tassinari, Aglioti, Chelazzi, Peru, & Berlucchi, 1994;Tassinari & Berlucchi, 1995).…”
Section: Modulation Of Peripheral Cueing Effects By Task Demandsmentioning
confidence: 99%
“…They reported that IOR was larger when target luminance was low than when it was high, and when the target modality was visual rather than auditory. Moreover, Lupiáñez et al (2007) carried out a study in which target frequency was manipulated; they introduced a frequent target (the letter X) on 75 % of the trials, and two different infrequent targets (the letters O and U) on 25 % of trials. Participants were instructed to detect the frequent target and to discriminate the identities of the other two, infrequent letters.…”
Section: Modulation By Target Characteristicsmentioning
confidence: 99%